2017
DOI: 10.1111/aab.12356
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Grapevine leafroll‐associated virus 3 on the physiology in asymptomatic plants of Vitis vinifera

Abstract: Grapevine leafroll disease is one of the most important viral diseases of grapevine (Vitis vinifera) worldwide. Grapevine leafroll-associated virus 3 (GLRaV-3) is the most predominant virus species causing this disease. Therefore, it is important to identify GLRaV-3 effects, especially in plants which do not systematically show visual symptoms. In this study, effects of GLRaV-3 on grapevine physiology were evaluated in asymptomatic plants of Malvasía de Banyalbufar and Cabernet Sauvignon cvs. Absolute virus qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 64 publications
3
9
0
Order By: Relevance
“…berries) and that the phloem is probably the main route of virus diffusion. Our results confirmed that GVB abundance can vary during the growing season, indicating that both climatic conditions and plant phenological stage play a key role in influencing virus movement within an infected vine and concentration, as indicated previously for other virus–grapevine genotype combinations (El Aou‐ouad et al., ; Gambino et al., ; Montero et al., ; Vega et al., ; Velasco et al., ). Of particular note, the GVB titre measured in ‘Albarossa’ berries was more than 1000 times higher than that in leaves collected at the end of the season.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…berries) and that the phloem is probably the main route of virus diffusion. Our results confirmed that GVB abundance can vary during the growing season, indicating that both climatic conditions and plant phenological stage play a key role in influencing virus movement within an infected vine and concentration, as indicated previously for other virus–grapevine genotype combinations (El Aou‐ouad et al., ; Gambino et al., ; Montero et al., ; Vega et al., ; Velasco et al., ). Of particular note, the GVB titre measured in ‘Albarossa’ berries was more than 1000 times higher than that in leaves collected at the end of the season.…”
Section: Discussionsupporting
confidence: 90%
“…The analysis of leaf physiological performances attested that net photosynthesis, stomatal conductance and substomatal CO 2 concentration were the main parameters affected by GVB, particularly at the end of the season. Nevertheless, GVB‐infected grapevines underwent a decrease in terms of physiological performance to a lesser extent than other grapevine–virus combinations (Guidoni et al., ; Mannini et al., ; Montero et al., ; Sampol et al., ). The overall picture of gas exchange measurements indicated a moderate metabolic, non‐stomatal, photosynthetic limitation in GVB‐infected plants in the absence of environmental and/or water limitation, in accordance with the results reported previously in GRSPaV‐infected grapevines (Gambino et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After GLRaV-3, the second and the third most abundant viruses in the present study were GRSPaV and GVA associated with the rugose wood complex disease. Confirming data from surveys carried out in the Mediterranean basin [ 26 , 27 ] as well as worldwide [ 28 , 29 ] GRSPaV was found in 81.69% of tested samples. However, although wide-spread, GRSPaV infection has no significant impact on growth and yields and potentially may be even beneficial to the grapevine host [ 30 ].…”
Section: Discussionsupporting
confidence: 72%
“…Changes to photosynthesis and carbohydrate metabolism in different tissues also represent a basic physiological response of grapevine, not only in presence of PM attack [35,43,54] but also under other plant diseases [34,44,45]. The enhanced activity of grape invertase genes coupled with the increased accumulation of soluble sugars in infected leaves most likely causes a shift in the sink-source balance that progressively slows down the Calvin cycle, with consequent serious reduction of the plant assimilation rates [44][45][46]55]. Although carbohydrate metabolism is globally down-regulated by AcS-Mt treatment in our samples, other specific categories of carbohydrate metabolic genes, mostly involved in sugar-primed signaling processes, were highly activated.…”
Section: Long-term Defense Responses Are Induced Following Applicatiomentioning
confidence: 99%